2021
DOI: 10.1017/jwe.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

On Fine Wine Pricing across Different Trading Venues

Abstract: This article examines how selected attributes of Bordeaux fine wines (producer, vintage, quality, bottle size, case, flaws, and transaction volume) affect prices in three types of trading venues: auctions, electronic exchange, and the over-the-counter (OTC) market. The findings indicate a price differentiation across the venues. Wine aging leads to relatively higher prices at auctions than on the electronic exchange or the OTC. There is a nearly linear relationship between prices and wine ratings, the stronges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Table 2 Other effects, which are omitted from the table for brevity of presentation, are consistent with expectations: nonstandard bottle sizes trade at a significant premium; prices are significantly higher during the fourth quarter; and wines sold as futures trade at a small discount (e.g., Oleksy, Czupryna, and Jakubczyk, 2021). Figure 1 illustrates the estimated relationship between aging and prices.…”
Section: B Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Table 2 Other effects, which are omitted from the table for brevity of presentation, are consistent with expectations: nonstandard bottle sizes trade at a significant premium; prices are significantly higher during the fourth quarter; and wines sold as futures trade at a small discount (e.g., Oleksy, Czupryna, and Jakubczyk, 2021). Figure 1 illustrates the estimated relationship between aging and prices.…”
Section: B Resultssupporting
confidence: 62%
“…Price and production quantity are clearly not perfectly correlated: Lafite is the biggest, while Haut Brion and Cheval Blanc are among the smallest. Other effects, which are omitted from the table for brevity of presentation, are consistent with expectations: nonstandard bottle sizes trade at a significant premium; prices are significantly higher during the fourth quarter; and wines sold as futures trade at a small discount (e.g., Oleksy, Czupryna, and Jakubczyk, 2021).…”
Section: Resultssupporting
confidence: 56%
“…If we choose a specific region in the North American wine market as a baseline, fine wines that come from France are sensitive to prices and can be sold at a premium, whereas others coming from other countries have almost no difference in price level [3]. A recent study examines the impact of different trading venues on wine prices; the characteristics of Bordeaux fine wines have various responses to affect transaction prices across three trading venues, which are auctions, electronic exchange market, and the OTC market [5].…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Wines are also analyzed in the macroeconomic environment. A study [5], for example, sheds light on macroeconomic factors of wine market pricing, such as real interest rates, the money supply, and the proportion of investment funds in GDP. Except for commodities in the industry, wines unfold many attributes of an investment.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…However, in the wine industry, traditionally and absolutely, many practitioners and academicians believed and reported that professional wine critics' wine grades, namely Robert Parker's wine scores, affect the market's wine prices and consumers' wine choices. Robert Parker's ratings effect on price and customer purchase behaviors are well documented in this industry [12][13][14][15][16][17]. In this regard, in the wine industry, we cannot insist that Collective Intelligence has overpowered wine critics in respect to knowledge and power for wine evaluation and price effect.…”
Section: Introductionmentioning
confidence: 99%